The Effectiveness of Aloe Vera Extract as A Natural Ingredient in Reducing Hair Loss - nurmagrianty, khandika cece; Agustin , Eny Widhia (JURNAL BIOSAINS, 2025)
Hair loss is a common condition affecting many individuals, particularly teenagers and women who wear the hijab. Aloe vera contains various bioactive compounds, including vitamins, proteolytic enzymes, and amino acids, which are known to nourish the scalp and stimulate hair growth. This study aims to evaluate the effectiveness of Aloe vera extract in different types of hair care formulations, such as shampoos, hair tonics, serums, and pomades, for treating hair loss. A qualitative descriptive literature review was conducted by analyzing 30 relevant national and international scientific articles published between 2016 and 2025. The findings indicate that Aloe vera has the potential to reduce hair loss, promote hair growth, and support scalp health. Furthermore, the combination of Aloe vera with other herbal ingredients, such as candlenut, celery, and lime, may enhance its efficacy. Products based on Aloe vera are also reported to have good physical stability, be safe for use, and be compatible with various scalp types. The study concludes that Aloe vera is a promising natural ingredient for the development of safe, effective, and sustainable herbal hair care products.